Aportes sobre la formación en investigación: Una mirada desde las practicas investigativas. (Revista de Diavulgación L'esprit Ingénieux, 2024)
The epistemological perspective from which the present text emerges implies a critical and insightful reading of the current context from which the positions and participants of the scientific ecosystem emerge. It is a proposal that embodies the " sentimental thoughts " of the new generations of researchers who claim spaces, their own spaces in the middle of the dominant scientific rationalities that have taken totalitarian control of the ways and means of knowledge production. Other ways of recognizing and constructing knowledge, societies, cultures and vehicles such as language, are presented and represented as scenarios on which participating realities, problems, contexts, among others, are continuously recreated as a fabric of realities. The other understandings that arise from qualitative changes in relationships are increasingly diffuse, as they are no longer interested in marking distinctions as before; on the contrary, debates now revolve around identities. They revolve around the unconditional recognition of the other as a legitimate other, not as an enemy or adversary to be eliminated; on the contrary, the other is assumed as a co-constructor and differential of oneself. This self is not defined but acquires characteristics that allow it to be in relation to others, that is, that allow it to coexist, to exist also in and for others.